Pengembangan Keterampilan Hard Skill Siswa Melalui Pelatihan Microsoft Excel di SMKS Al Muhajirin Arosbaya - Putri, Aurellia Maharani (Jurnal Pengabdian Masyarakat, 2024)
Microsoft Excel training at SMKS Al-Muhajirin arosbaya focuses on the importance of hard skills in the world of education and work, especially in the digital era and evolving technology. Mastery of microsoft excel is a skill that is needed in various sectors, especially in the field of administration and finance. Based on the results of the pre-test conducted on students of Class X TKJ SMKS Al-Muhajirin their Microsoft Excel skills are still very lacking, with the majority of students are in the category of" less "and"very less". Microsoft Excel training was conducted by quasi-experimental method involving 13 students of Class X TKJ SMKS Al-Muhajirin who took the pre-test and post-test. The training uses game-based learning method to improve student interaction and learning interest. Facilities used include a computer laboratory equipped with LCD, projector, and computers that have Excel installed. Based on the pre-test the majority of students were in the categories of "less" and "very less," showing very limited Excel skills. After the training, post-test results showed improvement, with 46% of students achieving "good" and "very good," as well as none of the students being in the "very less" category."The Excel skills taught during training are not only useful in the world of work, but also in everyday life, such as managing academic data, creating tables of values, to managing personal budgets. In conclusion, Microsoft Excel training at SMKS Al-Muhajirin arosbaya successfully improved students ' skills, equipping them with practical skills for industrial needs in the digital era.